Omicron-Associated Changes in Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Symptoms in the United Kingdom. (19th August 2022) - Vihta, Karina-Doris; Pouwels, Koen B; Peto, Tim E A; Pritchard, Emma; House, Thomas; Studley, Ruth; Rourke, Emma; Cook, Duncan; Diamond, Ian; Crook, Derrick; Clifton, David A; Matthews, Philippa C; et al.
Abstract: Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Delta variant has been replaced by the highly transmissible Omicron BA.1 variant, and subsequently by Omicron BA.2. It is important to understand how these changes in dominant variants affect reported symptoms, while also accounting for symptoms arising from other cocirculating respiratory viruses. Methods: In a nationally representative UK community study, the COVID-19 Infection Survey, we investigated symptoms in polymerase chain reaction (PCR)–positive infection episodes versus PCR-negative study visits over calendar time, by age and vaccination status, comparing periods when the Delta, Omicron BA.1, and BA.2 variants were dominant. Results: Between October 2020 and April 2022, a total of 120 995 SARS-CoV-2 PCR-positive episodes occurred in 115 886 participants, with 70 683 (58%) reporting symptoms. The comparator comprised 4 766 366 PCR-negative study visits (483 894 participants), with symptoms reported at 203 422 visits (4%). Symptom reporting in PCR-positive infections varied over time, with a marked reduction in loss of taste/smell as Omicron BA.1 dominated, which was maintained with BA.2 (44% symptomatic infections reporting loss of taste/45% symptomatic infections reporting loss of smell on 17 October 2021, 16%/13% 2 January 2022, 15%/12% 27 March 2022). Cough, fever, shortness of breath, myalgia, fatigue/weakness, and headache also decreased after Omicron BA.1 dominated, but sore throat increased, the latter to a greater degree than concurrent increases in PCR-negative visits. Fatigue/weakness increased again after BA.2 dominated, although to a similar degree to concurrent increases in PCR-negative visits. Symptoms were consistently more common in adults aged 18–65 years than in children or older adults. Conclusions: Increases in sore throat (also common in the general community), along with a marked reduction in loss of taste/smell, make Omicron harder to detect with symptom-based testing algorithms, with implications for institutional and national testing policies. Abstract : In a UK community study, loss of taste/smell was markedly less commonly reported with Omicron BA.1/BA.2 than with Delta severe acute respiratory syndrome coronavirus 2 infections, with smaller declines in reported shortness of breath, myalgia, and fatigue/weakness but increases in sore throat, challenging symptom-based testing algorithms.